Crystal structure-guided design of berberine-based novel chitinase inhibitors - Lei Chen; Ling Zhu; Jinli Chen; Wei Chen; Xuhong Qian; Qing Yang (Taylor & Francis Group, 2020)
Glycoside hydrolase family 18 (GH18) chitinases play an important role in various organisms ranging from bacteria to mammals. Chitinase inhibitors have potential applications as pesticides, fungicides, and anti-asthmatics. Berberine, a plant-derived isoquinoline alkaloid, was previously reported to inhibit against various GH18 chitinases with only moderate Ki values ranging between 20 and 70 μM. In this report, we present for the first time the berberine-complexed crystal structure of SmChiB, a model GH18 chitinase from the bacterium Serratia marcescens. Based on the berberine-binding mode, a hydrophobic cavity-based optimisation strategy was developed to increase their inhibitory activity. A series of berberine derivatives were designed and synthesised, and their inhibitory activities against GH18 chitinases were evaluated. The compound 4c showed 80-fold-elevated inhibitory activity against SmChiB and the human chitinase hAMCase with Ki values at the sub-micromolar level. The mechanism of improved inhibitory activities was proposed. This work provides a new strategy for developing novel chitinase inhibitors.